Apoptosis in development. - Meier, P.; Finch, A.; Evan, G. (Nature, 2000)
Essential to the construction, maintenance and repair of tissues is the ability to induce suicide of supernumerary, misplaced or damaged cells with high specificity and efficiency. Study of three principal organisms--the nematode, fruitfly and mouse--indicate that cell suicide is implemented through the activation of an evolutionarily conserved molecular programme intrinsic to all metazoan cells. Dysfunctions in the regulation or execution of cell suicide are implicated in a wide range of developmental abnormalities and diseases.